Health behaviours in young people from rural environments - Sygit, Katarzyna (Polish Journal of Public Health, 2009)
Aim. The following research aimed to study the health behaviours of young people living in rural environments.Materials and methods. The subjects were 2165 young people, along with their parents (2165), living in rural environments. Original questionnaires were used for the purpose of the study, and the information gathered then analysed using Chi-square, Cramer’s V and Spearman’s rho tests. Results. The majority of the subjects (75.15%) stated that their parents provided them with a varied and appropriate diet. Only 30% assessed their own diet as very good, with 9% evaluating it as satisfactory or poor (e.g. 30.49% of the subjects eat sweet foods seven times a week). In total, 39.63% of the subjects evaluated their health as very good and good. Among the subjects, passive leisure activities predominated (55.52%), and use of stimulants was widespread, with 10.67% smoking regularly, 50.07% drinking occasionally and 4.85% taking drugs. Their awareness of health issues was also evaluated; since 19.31% were unable to say what they should do to be healthy, this indicates a lack of knowledge in this area. Among the subjects’ parents, 28.91% stated that their children’s health was very good, with a further 57.60% stating that it was good. According to 21.43% of the parents, their children have a very good diet. However, 16.2% of the parents claimed that their children had started smoking, and 26.8% drinking.Conclusions. It was found that there were a variety of health behaviours in young people from rural environments, and that there were discrepancies in the assessment of health behaviours as seen by the subjects and their parents.